Recapturing fugitive power: epistemology, complexity and democracy (2004)
While policy network theory employs complexity concepts (self-regulation, emergence) mainly as explanatory tools, potential theoretical contributions arising from the underpinning analytical principles have been less explored. It is argued that by directly considering multi-level environmental governance as a far-from-equilibrium complex system, it is possible to explore how governance structures might better support and construe the dynamic and delicate conditions necessary for the presence of life. Problem formulation or 'agenda setting' powers exerted by civil servants and scientists are examined as emergent properties, systemic in and necessary for the stability of multi-level governance structures. Finally, it is proposed that multi-level environmental governance design may be improved through a reconceptualisation of representation, informed by principles from complexity theory, which embraces and 'recaptures' power exerted through extra-electoral governance relationships.